Improvements in acne and skin oiliness with tazarotene 0.045% lotion in patients with oily skin - Emil A. Tanghetti; Joshua A. Zeichner; Michael Gold; Neil Sadick; Fran E. Cook-Bolden; Leon H. Kircik; Linda Stein Gold; Jonathan Weiss; Stephen K. Tyring; James Q. Del Rosso; Eric Guenin (Journal of Dermatological Treatment, 2023)
Background Excessive sebum production is a factor in acne development. Tazarotene 0.045% lotion has demonstrated reductions in acne lesions and acne-induced sequelae. Objective Evaluate efficacy, changes in skin oiliness, and safety with tazarotene 0.045% lotion in participants with moderate-to-severe acne and oily skin. Methods In two phase 3, double-blind, 12-week studies (NCT03168321; NCT03168334), participants aged ≥ 9 years with moderate-to-severe acne were randomized 1:1 to once-daily tazarotene 0.045% lotion or vehicle lotion (N = 1614). This pooled, post hoc analysis included only participants self-categorized with oily skin at baseline on the Acne-Specific Quality of Life questionnaire item 19 (scores: 0 [extremely oily] to 6 [not at all oily]). Inflammatory/noninflammatory lesion counts, treatment success, skin oiliness, treatment-emergent adverse events (TEAEs), and cutaneous safety/tolerability were evaluated. Results In all participants with oily skin (n = 793), tazarotene provided greater reductions in inflammatory/noninflammatory lesions (p < 0.001, both) and greater treatment success rates versus vehicle (p < 0.01) at week 12. Over two-thirds of polymeric lotion-treated participants had subjective skin oiliness reductions by week 12, with around a third reporting ‘low/not’ oily skin. Tazarotene TEAE rates were similar to the overall population. Conclusions Once-daily treatment with tazarotene 0.045% polymeric emulsion lotion may help improve patient-perceived skin oiliness in those with moderate-to-severe acne.